The Process of Triple Elimination Program Implementation in Antenatal Care Batang Regency: Qualitative Study - Yulfiana; Chriswardani Suryawati; Ayun Sriatmi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The Maternal Mortality Rate (MMR) of Batang Regency in 2023 is still high. Many efforts have been made to reduce the mortality of pregnant women and babies born with integrated ANC services, but have not received optimal results. Objective: The purpose of this study is to analyze aspects of the process including planning, organizing, implementing and assessing in the triple elimination program. Methods: The study used qualitative methods with process variables consisting of planning, organizing, implementing and assessing in a triple elimination program. Data collection through in-depth interviews with 8 main informants and 10 triangulation informants. The main informants are Midwives, Coordinators, and Analysts of the triple elimination program in 4 selected Puskesmas. Triangulated informants are selected based on management level. District level to the Head of Kesga and P2P Dinkes Batang, Puskesmas level to 4 selected Puskesmas Heads and grass-root level to 4 mothers who receive integrated ANC service benefits at Puskesmas. The instrument uses an interview guide. Analysis using qualitative descriptive methods. Results: Planning is carried out in stages from the implementation of activities, namely the integrated ANC team of the Puskesmas by calculating needs. Furthermore, it was discussed with the team and submitted to the Head of the Puskesmas which was then submitted to the District through the Batang Health Office. Organizing is done from the Coordinator Midwife who manages his team. Team management is discussed together and approved by the Head of Puskesmas. Implementation is carried out in accordance with applicable SOPs. The triple elimination assessment is good but there needs to be improvement. Especially in the refusal of triple elimination examination from pregnant women during the implementation of the program. Conclusion: The triple elimination program process in Batang Regency has been good. There needs to be a strategy to invite all pregnant women so that there is no rejection of the triple elimination program.